2007
DOI: 10.1002/anie.200701419
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium Dispersion during NO/CO Conversions

Abstract: The catalyzed reaction between NO and CO for NO x removal is a key component of the role of rhodium in automotive exhaust catalysts.[1] Kinetic models for this reaction have been reported [2] with structural inferences based on Rh(111). Surface-science studies have provided elegant descriptions of surface oxidation (by O 2 ).[3] However, the mean nuclearity of the metal on Rh/Al 2 O 3 during the reduction of NO by H 2 varies with gas partial pressures and temperature.[4] Hence, an assumption of an invariant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 25 publications
2
63
0
Order By: Relevance
“…16,54 It results in two bands in the CO IR spectrum: one in-phase CO stretching vibration between 2118 and 2070 cm -1 and one out-of-phase stretching vibration between 2053 and 2007 cm -1 . 6,[12][13][14][15][16][17][18]30,31,[33][34][35][43][44][45][46][48][49][50][51][52][53][54][55][56] Next to these, linearly bonded CO adsorbed on Rh metallic particles has been reported to give rise to a band between 2075 and 2031 cm -1 , whereas CO linearly adsorbed on oxidized Rh 1+ or Rh 2+ crystallites is attended with a band between 2135 and 2110 cm -1 . 6,12,[15][16][17]19,[32][33][34][43][44][45][46][47][48][49][50][51]53 In order to unambiguously assign...…”
Section: Resultsmentioning
confidence: 99%
“…16,54 It results in two bands in the CO IR spectrum: one in-phase CO stretching vibration between 2118 and 2070 cm -1 and one out-of-phase stretching vibration between 2053 and 2007 cm -1 . 6,[12][13][14][15][16][17][18]30,31,[33][34][35][43][44][45][46][48][49][50][51][52][53][54][55][56] Next to these, linearly bonded CO adsorbed on Rh metallic particles has been reported to give rise to a band between 2075 and 2031 cm -1 , whereas CO linearly adsorbed on oxidized Rh 1+ or Rh 2+ crystallites is attended with a band between 2135 and 2110 cm -1 . 6,12,[15][16][17]19,[32][33][34][43][44][45][46][47][48][49][50][51]53 In order to unambiguously assign...…”
Section: Resultsmentioning
confidence: 99%
“…Originally developed at the University of Southampton, UK, [6][7][8][9][10] a resource of this type is now implemented on ID24 (dispersive EXAFS) a the ESRF, Grenoble [11,12]. It is, however, a mobile experiment and can be utilised at other beamlines.…”
Section: Introductionmentioning
confidence: 97%
“…Synchronously applied combinations of structurally direct X-ray based techniques, such as EXAFS, XRD, and SAXS/WAXS, together with vibrational spectroscopies (such as Raman [2][3][4][5] and infrared spectroscopies [6][7][8][9][10][11][12]), and techniques that give a global overview of catalytic performance (such as mass spectrometry and gas chromatography), are particularly attractive. A number of these types of experiments [2][3][4][5][6][7][8][9][10][11][12] have now been demonstrated, and it seems certain that they will become ever more powerful as the process of refining them, and developing M. A. Newton (&) The European Synchrotron Radiation Facility, 6 Rue Jules Horowitz, BP-220, Grenoble 38043, France e-mail: newton@esrf.fr new ones, continues in response to the ever increasing desires of the catalysis, chemistry, and wider material science communities.…”
Section: Introductionmentioning
confidence: 99%
“…However, metal nanoparticles are expected to not only provide highencounter fields but show peculiar performance originated in nanometer scale. Many studies about metal nanoparticles have revealed that various and unique structural changes are induced in metal nanoparticles themselves by changing temperature and/or atmosphere [1][2][3][4][5][6][7][8]. These results indicate that observation of metal nanoparticles under only normal atmospheric condition may cause limited understandings of metal nanoparticles especially about the mechanism of surface catalytic reaction.…”
Section: Introductionmentioning
confidence: 99%